Importance of geotechnical diagnosis in railway management: A review - Jorge Rojas Vivanco; Pierre Breul; Aurélie TALON; Miguel Angel Benz-Navarrete; Sébastien Barbier; Younes Haddani (Transportation Engineering)
Railway tracks, like all civil works, experience degradation after being put into service, thus losing their initial design conditions. This degradation manifests itself mainly through misalignment and specific deterioration mechanisms of each component, which reduces safety and comfort during the passage of trains. In order to maintain their operational capabilities or prolong their service life, continuous monitoring, diagnosis and maintenance processes are carried out. These actions aim to restore the physical, mechanical and geometrical properties necessary for track operation.In practice, rail managers often employ hegemonic techniques such as geometric measurements to detect defects and routine maintenance to realign, known as tamping. Although these practices have proven to be effective, in some cases they do not technically and economically competently solve the root problem. For this reason, diagnosis should be multidisciplinary and incorporate various disciplines associated with the track components.This paper aims to highlight the importance and impact of geotechnical diagnosis in the management of railway networks. To achieve this, the article has the following structure: (a) Railway track components: the main elements of the track are described and the role of geotechnical components in the stability of the infrastructure is highlighted, (b) Track degradation: The main deterioration of the track, such as loss of geometry, and its relation to the wear of the geotechnical elements are addressed, (c) Monitoring and monitoring: the most commonly used geotechnical inspection methods and their effectiveness in the analysis of granular material are presented, (d) Geotechnical diagnosis: Current maintenance management is analyzed and guidelines for a comprehensive diagnosis are suggested, highlighting cases where poor assessment has generated problems, (e) Maintenance techniques: Preservation methods are reviewed, stressing the importance of accurate diagnosis for their effectiveness, and (f) Future perspectives: Trends such as the use of artificial intelligence and advanced data management in the railway sector are explored.